2014
DOI: 10.1155/2014/656937
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variability of Wild Cardoon (Cynara cardunculus L. var. sylvestris) Populations in North of Tunisia

Abstract: In north of Tunisia, wild cardoon (Cynara cardunculus L. var. sylvestris (Lamk) Fiori) is called “khurshef.” It is consumed mainly for its fleshy stems and leafstalks in some traditional dishes. In some regions, heads were used to prepare cheese. North Tunisian germplasm has been currently damaged by severe genetic erosion, pollution, urbanization, and bad farming practices. In order to preserve this species and to assess morphological relationship between accessions, the present study aims to prospect and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In this study, the most part of genetic variation was found within populations and a considerable level of gene exchange was observed between populations. According to the high level of genetic diversity proved in a previous study (Ben Ammar et al, 2014), it would be very interesting to manage these genetic resources by the establishment of an ex situ collection. Moreover, it would be useful to complete this work by estimating the genetic diversity of this understudied germplasm using biochemical and other morphological characterization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the most part of genetic variation was found within populations and a considerable level of gene exchange was observed between populations. According to the high level of genetic diversity proved in a previous study (Ben Ammar et al, 2014), it would be very interesting to manage these genetic resources by the establishment of an ex situ collection. Moreover, it would be useful to complete this work by estimating the genetic diversity of this understudied germplasm using biochemical and other morphological characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the study conducted by Ben Ammar et al (2014) and Khaldi et al (2012) has revealed a large variability among wild cardoon populations. Therefore, the objective of this http://dx.doi.org/10.1016/j.scienta.2015.01.017 0304-4238/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…For the lesser dormant population, a similar treatment duration resulted in total dormancy loss, without induction into secondary dormancy with extended storage. Differences among C. cardunculus populations were already described for many attributes (Ben Ammar et al ., ), for instance tolerances to abiotic stress (Raccuia et al ., ) and chemical profiles (Portis et al ., ). Here, differences between populations were recorded for the first time for response to temperature‐dependent dormancy release.…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the experiments were performed using achenes collected in Olavarr ıa in 2015 and 2016. For this set of experiments, achenes were cleaned and immediately stored at À18°C to maintain their initial dormancy level (Benech-Arnold et al, 2006) until used in the experiments.…”
Section: Achenes Collectionmentioning
confidence: 99%
See 1 more Smart Citation